ALTERNARIA DISEASE OF POTATO AND ITS CONTROL (REVIEW) - Z.Z.Yuldashova; B.S.Sodikov, U.K.Khamiraev (EPRA International Journal of Research and Development (IJRD), 2023)
Diseases caused by Alternaria fungi are considered one of the most common and dangerous diseases of many plants around the world. These fungi primarily damage annual plants, especially vegetable crops, as well as leaves, stems, flowers and fruits of fruit trees and crops. The damage caused by Alternaria fungi in various plants is among the highest yield losses of any pathogen. This review provides general information on potato Alternaria disease, its causative agent, prevalence, development, its effect on yield, and control measures against it. When we analyzed the information provided by world phytopathologists, it became clear that the Alternaria solani fungus is one of the main pathogens that damage all green parts of potatoes and tubers. Air temperature of 22...26 ºC is optimal for the development of the disease. As a result of the strong development of the disease, the yield can be reduced to 5-78%.